Implementasi Pembelajaran Berbasis Masalah dengan Media Video sebagai Strategi Peningkatan Kemampuan Berpikir Kritis Peserta Didik pada Materi IPAS - Lestari, Dewi; Achmad, Firdaus; Setyaningrum, Vidya (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
Critical thinking is one of the essential skills that must be nurtured from the early stages of formal education, especially in responding to the increasing complexity of information flow. In practice, however, elementary school students often struggle to analyze problems, construct logical reasoning, and draw conclusions from given information. This study aimed to enhance students’ critical thinking skills by implementing a Problem-Based Learning (PBL) model integrated with video media in the Natural and Social Sciences (IPAS) subject. The research employed a Classroom Action Research (CAR) method with a quantitative approach, conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 30 fourth-grade students at SDN 03 Pontianak Timur. Data were collected through critical thinking tests, observation sheets, and documentation. The results indicated an increase in mastery from 27% in the pre-action stage, to 60% in Cycle I, and reaching 83% in Cycle II. The implementation of PBL supported by video media proved effective in fostering students’ active engagement and gradually strengthening their critical thinking abilities.